Empowering women farmers’ groups through cocoa pod cracker innovation - Managanta, Andri Amaliel; Lantu, Ika Paramitha; Sriwati, Ni Kadek; Loliwu, Yan Alpius (Community Empowerment, 2025)
Cocoa pod husk waste in Kageroa Village, Poso, remains underutilized and poses environmental challenges. This community empowerment program aims to transform this waste into an innovative food product—cocoa husk crackers—to enhance the income and entrepreneurial skills of the Sukamaju Mohintuwo Women Farmer Group (KWT). The program employed a participatory approach, including food processing technology training, production mentoring, and evaluation. Results showed a significant increase in partners' capacity across knowledge (from 45.8 to 85.7), attitude (39.4 to 88.1), and skills (58.6 to 89.3). Furthermore, the group successfully produced crackers with competitive texture, taste, and shelf life. This initiative proved effective in shifting the community’s mindset regarding cocoa waste, creating new business opportunities, and strengthening women's roles in the local economy through regional commodity-based innovation.